Micralymma marinum - Majka, Christopher; Klimaszewski, Jan; Lauff, Randolph (Zenodo, 2008)
Micralymma marinum (Ström, 1785) NOVA SCOTIA: Guysborough Co.: Tor Bay, 6.V.1996, R.F. Lauff, intertidal zone, (1, NSMC). This species is newly recorded in Nova Scotia and its distribution in Atlantic Canada is shown in Fig. 12. It is a widely distributed Holarctic species found in intertidal habitats throughout Europe, Russia, Iceland, Greenland, Atlantic Canada, and New England in the USA (Larsson and Gígja 1959; Thayer 1985; Böcher 1988; Campbell and Davies 1991; Downie and Arnett 1996; Herman 2001). Böcher (1988, 34) wrote, “ M. marinum is a true marine insect, presumably spending its entire life cycle in the tidal zone, where it is regularly submerged at high tide. Adults and larvae are generally found together, on vertical parts or the underside of stones and rocks …”. Adults and larvae are predaceous, feeding on Collembola such as Anurida maritima (Guérin-Méneville, 1836), mites, and Thysanura although it is possible that larvae are, at least in part, also phytophagous feeding on algae (Thayer 1985; Böcher 1988; Hammond 2000). Published as part of Majka, Christopher, Klimaszewski, Jan & Lauff, Randolph, 2008, The coastal rove beetles (Coleoptera, Staphylinidae) of Atlantic Canada: a survey and new records, pp. 115-150 in ZooKeys 2 (2) on page 121, DOI:10.3897/zookeys.2.2, http://zenodo.org/record/576408